Sediment Features and Human Activities Structure the Surface Microbial Communities of the Venice Lagoon - Banchi, Elisa; Del Negro, Paola; Celussi, Mauro; Malfatti, Francesca (Frontiers in Marine Science, 2021)
Sediment microbial communities play essential roles in marine ecosystem functioning. Their study is crucial to understand how environmental conditions affect microbial diversity and biogeochemical cycles. The Venice Lagoon, one of the largest Adriatic transitional systems, is subjected to different natural and anthropogenic stressors. In this study, surface sediments microbial communities were finely characterized using 16S rRNA gene amplicon sequencing and metagenomics. Samples were collected seasonally in 2019 and 2020 at different sites within Lagoon sub-basins. Our results indicated a stable spatial distribution of the sediment microbiome: salinity, grain size, and total organic carbon were found to be important drivers in shaping prokaryotic communities, while temperature had a minor role. We detected high microbial diversity at all stations, mainly due to low abundant taxa: bacteria represented the vast majority of the reads (∼96.1%), with Woeseia the most abundant genus (∼4.4%). The metagenomic analysis highlighted significant differences among sites in terms of biogeochemical processes (e.g., C, N, Fe, and S metabolism), and cell-cell interaction strategies (e.g., mobilome, regulations and cell signaling). Chioggia, a sandy site subjected to marine influence, presented the highest abundance of ammonia-oxidizing archaeon Candidatus Nitrosopumilus, in accordance with the highest amount of ammonia monooxygenase subunit genes. At the same site, sulfate-reducing bacteria (Desulfobacteria and Desulfobacterales) and sulfur-related genes were found in lower abundance. Marghera and Tresse, the most polluted sites, showed higher abundance of sewage-related bacteria and antibiotic and toxic compound resistance genes. Furthermore, these sites showed higher amount of genes related to cell-cell interaction, such as pathogenicity islands, transposable-elements, and biofilm formation. Our findings highlighted that sediment features and human-related activities have profound and long-term impacts on the surface sediment microbial communities of the Venice Lagoon.